Factors Influencing the Attitudes of Rice Farmers in Langrod County towards Organic Agriculture - Fatemeh Askari Bozayeh (Journal of Biotropical Research and Nature Technology, 2024)
This research seeks to answer these questions, what are the attitudes of rice farmers in the field of organic farming and what factors influence their attitudes. The statistical population consisted of 500 rice farmers from three mainly rice-growing villages of Langrod county, Gilan province, and the sample size was 211. To select this sample size, simple random sampling was used. The data was collected through a questionnaire. Its face validity was based on a survey of expert opinions. To determine the reliability of the measurement tool, face-to-face interviews were conducted with a sample of 30 people outside of the main sample, and the calculated Cronbach's alpha coefficients confirmed the research tool. Descriptive statistics, correlation tests, and factor analysis were used in SPSS 22 software to analyze the data. Deviation distance from the mean method was used to group the attitudes of rice farmers. The results showed that 18% of the respondents have a negative attitude towards organic agriculture, about 70% have a somewhat positive attitude, and about 12% have a completely positive attitude, and the attitude of the surveyed farmers is influenced by the factors of caring for nature and preserving the soil fertility, the quality and quantity of agricultural products, the value and importance of rural landscapes, traditionalism, the desire to preserve past customs and traditions, and the impact of personal experiences which account for 19.60, 11.44, 9.25, 9.06 and 8.98 percent of the explained variance, respectively.